Housing programmes for Eskimos in Northern Canada - Yates, A. B. (Polar Record, 1970)
The Government of Canada began supplying housing for some of its Eskimo people in the Northwest Territories in 1956. At this date the majority of Eskimos still followed their traditional nomadic way of life and lived in igloos or snow houses during winter, and in skin or canvas tents during summer. Since 1956, the tendency of Eskimo families to settle in the vicinity of trading posts, church missions, and newly established federal schools has increased, and the problem of providing permanent accommodation for them has been aggravated. At first the new townsmen improvised shelters from a combination of tents, packing cases, and scraps of metal, tar paper and lumber. When these inadequate dwellings were used as permanent residences, grave social and public health problems resulted from overcrowding.